Preoperative Standardized Uptake Value of Metastatic Lymph Nodes Measured by 18F-FDG PET/CT Improves the Prediction of Prognosis in Gastric Cancer. Issue 26 (July 2015) - Song, Bong-Il; Kim, Hae Won; Won, Kyoung Sook; Ryu, Seung Wan; Sohn, Soo Sang; Kang, Yu Na
Abstract : Abstract: This study assessed whether preoperative maximum standardized uptake value (SUVmax) of metastatic lymph nodes (LNs) measured by 18 F-fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) could improve the prediction of prognosis in gastric cancer. One hundred fifty-one patients with gastric cancer and pathologically confirmed LN involvement who had undergone preoperative 18 F-FDG PET/CT prior to curative surgical resection were retrospectively enrolled. To obtain nodal SUVmax, a transaxial image representing the highest 18 F-FDG uptake was carefully selected, and a region of interest was manually drawn on the highest 18 F-FDG accumulating LN. Conventional prognostic parameters and PET findings (primary tumor and nodal SUVmax) were analyzed for prediction of recurrence-free survival (RFS) and overall survival (OS). Furthermore, prognostic accuracy of survival models was assessed using c-statistics. Of the 151 patients, 38 (25%) experienced recurrence and 34 (23%) died during follow-up (median follow-up, 48 months; range, 5–74 months). Twenty-seven patients (18%) showed positive 18 F-FDG nodal uptake (range, 2.0–22.6). In these 27 patients, a receiver-operating characteristic curve demonstrated a nodal SUVmax of 2.8 to be the optimal cutoff for predicting RFS and OS. The univariate and multivariate analyses showed that nodal SUVmax (hazard ratio [HR] = 2.71, P  < 0.0001), pathologic N (pN) stage (HR = 2.58, P  = 0.0058), and pathologic T (pT) stage (HR = 1.77, P  = 0.0191) were independent prognostic factors for RFS. Also, nodal SUVmax (HR = 2.80, P  < 0.0001) and pN stage (HR = 2.28, P  = 0.0222) were independent prognostic factors for OS. A predictive survival model incorporating conventional risk factors (pT/pN stage) gave a c-statistic of 0.833 for RFS and 0.827 for OS, whereas a model combination of nodal SUVmax with pT/pN stage gave a c-statistic of 0.871 for RFS ( P  = 0.0355) and 0.877 for OS ( P  = 0.0313). Nodal SUVmax measured by preoperative 18 F-FDG PET/CT is an independent prognostic factor for RFS and OS. Combining nodal SUVmax with pT/pN staging can improve survival prediction precision in patients with gastric cancer.